Antimicrobial Study of Phenyl Substituted 4-Oxoacids - Sikkander, G. (Asian Journal of Chemistry, 2010)
Phenyl substituted 4-oxoacids were prepared by Friedel-Craft's reaction between substituted benzene with succinic anhydride in presence of anhydrous aluminium chloride. These compounds were tested in vitro for their antibacterial activity against gram positive bacteria (S. aureus and S. subtilis) and gram negative bacteria (E. coli and P. aeruginosa). The MIC values were determined by using serial dilution method.